Long-Term Persisting SARS-CoV-2 RNA and Pathological Findings: Lessons Learnt From a Series of 35 COVID-19 Autopsies - Maccio, Umberto; Zinkernagel, Annelies S.; Schuepbach, Reto; Probst-Mueller, Elsbeth; Frontzek, Karl; Brugger, Silvio D.; Hofmaenner, Daniel Andrea; Moch, Holger; Varga, Zsuzsanna (Frontiers in Medicine, 2022)
Background Long-term sequelae of coronavirus disease 2019 (COVID-19), including the interaction between persisting viral-RNA and specific tissue involvement, pose a challenging issue. In this study, we addressed the chronological correlation (after first clinical diagnosis and postmortem) between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA and organ involvement. Methods The presence of postmortem SARS-CoV-2 RNA from 35 complete COVID-19 autopsies was correlated with the time interval between the first diagnosis of COVID-19 and death and with its relationship to morphologic findings. Results Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA can be evident up to 40 days after the first diagnosis and can persist to 94 hours after death. Postmortem SARS-CoV-2 RNA was mostly positive in lungs (70%) and trachea (69%), but all investigated organs were positive with variable frequency. Late-stage tissue damage was evident up to 65 days after initial diagnosis in several organs. Positivity for SARS-CoV-2 RNA in pulmonary swabs correlated with diffuse alveolar damage (p = 0.0009). No correlation between positive swabs and other morphologic findings was present. Cerebral (p = 0.0003) and systemic hemorrhages (p = 0.009), cardiac thrombi (p = 0.04), and ischemic events (p = 0.03) were more frequent in the first wave, whereas bacterial pneumonia (p = 0.03) was more prevalent in the second wave. No differences in biometric data, clinical comorbidities, and other autopsy findings were found. Conclusions Our data provide evidence not only of long-term postmortem persisting SARS-CoV-2 RNA but also of tissue damage several weeks after the first diagnosis of SARS-CoV-2 infection. Additional conditions, such as concomitant bacterial pulmonary superinfection, lung aspergillosis, thromboembolic phenomena, and hemorrhages can further worsen tissue damage.